The Sopranos. The complete fourth season [videorecording (DVD)] - Chase, David, 1945 August 22-; Gandolfini, James; Bracco, Lorraine, 1955-; Falco, Edie (HBO Video, 2003)
It's tough times in Jersey for Tony Soprano. The sluggish economy hasn't been good for the family business. His wife, Carmela, is angling for more financial security. Some long-time lieutenants aren't happy with Tony's recent decisions. A rival boss wants a bigger piece of the suburban pie. A Soprano is actually heading to trial for the first time in decades. At least one child has lost interest in higher education.